Relationship of critical velocity to marathon running performance - Florence, S. L.; Weir, J. P. (European Journal of Applied Physiology, 1997)
The purpose of this investigation was to evaluate the critical velocity (CV) test for prediction of marathon running performance. The purpose of this investigation was to evaluate the critical velocity (CV) test for prediction of marathon running performance.